Kemasukan Islam ke Arkipelago Melayu: Kajian Pemikiran Hamka dalam Sejarah Umat Islam: The Entry of Islam into the Malay Archipelago: A Study of Hamka's Thoughts in the History of the Muslim Community - Amir, Ahmad Nabil (Al-Basirah Journal, 2022)
This paper discusses the history of the entry of Islam into the Malay region as recorded by Hamka in Sejarah Umat Islam and Dari Perbendaharaan Lama. In his significant research on the development of Islam in the archipelago, Hamka firmly maintains the statement that Islam entered this region in the 7th century AD from Arabia, and rejects the thesis that Islam was spread in the 13th century from Gujarat. This is defended by significant historical sources that prove that Islam has gained a foothold in the Malay world as early as the 7th century. This paper will analyse Hamka's thoughts on the development of the earliest history of Islam in the Malay world which is disgraced and debated in detail in his work, and compares it with Syed Muhammad Naquib al-Attas's analysis of Islam in Malay History and Culture which defends the same thesis.